High glucose induces alternative activation of macrophages via PI3K/Akt signaling pathway. (4th July 2017) - Wang, Jie; Liu, Jingjing; Wang, Yuying; Lin, Minghui; Tian, Wei; Zhou, Lingling; Ye, Xiaoyin; Lin, Lihang
Abstract: Objective: It has been proved that lactate-4.25% dialysate could result in peritoneal fibrosis by inducing alternative activation of macrophages in our previous study, but the mechanism of high glucose-induced alternative activation has not been elucidated. This study was, therefore, to investigate the mechanism by high glucose stimuli. Methods: In this study, Raw264.7 (murine macrophage cell line) cells were cultured and stimulated by 4.25% glucose medium, and mannitol medium was used as osmotic pressure control. Cells were harvested at 0 h, 4 h, 8 h, and 12 h to examine the expression of Arg-1, CD206, and p-Akt. After blocking PI3K by LY294002, the expression of Arg-1, CD206, and p-Akt was examined again. Results: The expression of Arg-1 and CD206 was increased in a time-dependent manner induced by high glucose medium. On the contrary, there was mainly no Agr-1 or CD206 expressed in cells cultured in the mannitol medium with the same osmotic pressure. What's more, Akt was phosphorylated at the eighth hour stimulated by high glucose medium, and LY294002 inhibited the expression of Arg-1 and CD206 by blocking the phosphorylation of Akt. Conclusions: Our study indicated that high glucose rather than high osmotic pressure induced M2 phenotype via PI3K/Akt signaling pathway.